2015
DOI: 10.3389/fmicb.2015.00691
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ protein profile analysis of neuroblastoma (NA) cells infected with the rabies viruses rHep-Flury and Hep-dG

Abstract: The rabies virus (RABV) glycoprotein (G) is the principal contributor to the pathogenicity and protective immunity of RABV. In a previous work, we reported that recombinant rabies virus Hep-dG, which was generated by reverse genetics to carry two copies of the G-gene, showed lower virulence than the parental virus rHep-Flury in suckling mice with a better immune protection effect. To better understand the mechanisms underlying rabies virus attenuation and the role of glycoprotein G, isobaric tags for relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 65 publications
2
12
0
Order By: Relevance
“…Therefore, AAK1 is involved in the entry of viruses via its function of regulating clathrin-mediated endocytosis. In our previous study, we showed that RABV infection increases AP-2-associated protein kinase 1 (AAK1) expression in mouse neuroblastoma (N2a) cells through proteomics analysis based on isobaric tags for relative and absolute quantitation (iTRAQ) [27]. In this study, we further confirmed the role of AAK1 in RABV infection.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Therefore, AAK1 is involved in the entry of viruses via its function of regulating clathrin-mediated endocytosis. In our previous study, we showed that RABV infection increases AP-2-associated protein kinase 1 (AAK1) expression in mouse neuroblastoma (N2a) cells through proteomics analysis based on isobaric tags for relative and absolute quantitation (iTRAQ) [27]. In this study, we further confirmed the role of AAK1 in RABV infection.…”
Section: Introductionsupporting
confidence: 75%
“…Our previous study showed that rabies viruses (HEP-Flury strain and rHEP-dG strain) proliferation increased AAK1 expression in N2a cells by iTRAQ protein profile analysis [27]. To confirm these results, N2a cells were infected with RABV rHEP-GFP, which carries a green fluorescent protein gene between the N and P genes [29], to investigate the expression of AAK1.…”
Section: Rabv Infection Enhanced the Aak1 Expressionmentioning
confidence: 91%
“…Cell apoptosis is a particular factor attenuating the pathogenic potential of RABV ( Préhaud et al, 2003 ; Thoulouze et al, 2003 ; Kassis et al, 2004 ). Previous work has shown that, at a MOI of 0.01, rHEP-Flury does not cause toxicity in NA cells, and only induced 2.9% NA cell apoptosis at 48 h post-infection ( Yang et al, 2015b ; Peng et al, 2016 ). In this study, at a MOI of 3, the percentage of early stage apoptotic cells as well as late stage apoptotic or even necrotic cells was about 11.8%.…”
Section: Resultsmentioning
confidence: 92%
“…Meanwhile, we found that the RABV P4 which G mRNA ratio increased, its pathogenicity was significant weaker than others. As HEP-Flury G protein could induce cell apoptosis which was contribute to attenuate the pathogenicity of RABV ( Yang et al, 2015b ; Peng et al, 2016 ). We speculated that the pathogenicity of RABV was correlated with the ratio of viral gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation